Comparative Analysis of Infrastructure Integration and Development in East and Southern Africa and Latin America - Haruna, Salum Mussa; Ntali, Agostinho Vontade; Guambe, Clesio de Anacleta Henriqueta; Omar, Mamudo Antonio; Paya, Eugenio Daniel (Technium Social Sciences Journal, 2025)
Cross-border infrastructure is one of the main drivers of regional integration and development in Eastern and Southern Africa but suffers from institutional fragmentation, asymmetric connectivity, and dependence on external finance. This study applies a comparative qualitative approach, based on expert interviews and document evidence, to examine integration policies in East and Southern Africa and derive lessons from Latin American experiences, including IIRSA, COSIPLAN, and regional energy integration. Drawing on endogenous development and dependency theory, the paper mentions everlasting setbacks—misaligned tariffs, rural infrastructure gaps, and ineffective policy coordination—via transport, energy, telecommunication, and water sectors. Latin America deserves credit for its application of public–private partnerships, long-term planning, and supranational coordination that offers adaptable lessons. The case made herein is that the agenda for infrastructure in Africa should transcend the physical investment by embedding governance, sustainability, and institutional consistency. The paper suggests an adaptive framework based on African realities and South–South comprehension, with infrastructure as a strategic tool for inclusive growth, political autonomy, and regional integration.